1994
DOI: 10.1016/s0022-5347(17)32638-1
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Sclerosus et Atrophicus Causing Phimosis in Boys: A Prospective Study with 5-Year Followup After Complete Circumcision

Abstract: We prospectively investigated 100 pediatric patients suffering from phimosis and found a 10% incidence of lichen sclerosus et atrophicus. This condition usually can be diagnosed preoperatively because of its classic manifestation of severe phimosis due to a sclerotic, whitish ring at the tip of the prepuce, which in our cases was accompanied by sclerogenous glanular lesions. To our knowledge our study represents the first evidence that the development of secondary phimosis with no apparent reason in school-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 13 publications
4
75
0
4
Order By: Relevance
“…27 20 The clinical intercurrences that patients with phimosis may present are: balanoposthitis, UTI and paraphimosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 20 The clinical intercurrences that patients with phimosis may present are: balanoposthitis, UTI and paraphimosis.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Alguns estudos 19,20 demonstraram incidência de LE em pacientes pediátricos com fimose, submetidos à postectomia, em torno de 15%. Porém, os dados não são precisos, devido ao fato de que o tecido removido na circuncisão é raramente examinado histologicamente e porque a operação é geralmente curativa, sem recorrência do quadro.…”
Section: Methodsunclassified
“…Meatal or urethral involvement is more likely with a history of previous surgery and was seen in 27% in the series by Gargollo et al [168]. The incidence of this condition is underestimated and recent evidence suggests that in boys referred with a diagnosis of phimosis the incidence ranges between 10-40 % [169][170][171][172]. In a series of 100 boys referred for phimosis, the incidence of LS was 1.8% under 6 years of age and up to 21% in those older [171].…”
Section: Genital Lichen Sclerosismentioning
confidence: 97%
“…The incidence of this condition is underestimated and recent evidence suggests that in boys referred with a diagnosis of phimosis the incidence ranges between 10-40 % [169][170][171][172]. In a series of 100 boys referred for phimosis, the incidence of LS was 1.8% under 6 years of age and up to 21% in those older [171]. In another prospective 10-year study by Kiss et al, the incidence of histologically confirmed LS was 40%, and 93% of LS patients had a history of secondary phimosis [170].…”
Section: Genital Lichen Sclerosismentioning
confidence: 99%
“…Zabieg obrzezania jest skuteczny w przypadku zmian LS zlokalizowanych na napletku i żołędzi [42][43][44]. W przypadku LS z dużymi zmianami zarostowymi utrudniającymi oddawanie moczu wykonuje się operacje ujścia cewki moczowej lub całej cewki moczowej usprawniające funkcjonowanie narządu [43,[45][46][47][48].…”
Section: Leczenie Drugiego Rzutuunclassified